Adherence of inactivated polio vaccine immunization for children in Central Java Province - Sriatmi, Ayun; Martini, Martini; Patriajati, Sutopo; Budiyono, Budiyono; Handayani, Novia; Kusumawati, Aditya; Armunanto, Armunanto (Intelektual Pustaka Media Utama, 2024)
Indonesia is a country with high-risk polio transmission. Administering inactivated polio vaccination (IPV) after drops-polio or oral polio vaccination (OPV) was a strategy stopping polio transmission because its ability to ward off poliovirus which was very dangerous. The IPV coverage was very low and have never reached the target since it was launched in 2016. The study purpose was analyzing determinants factors of IPV adherence. A cross-sectional survey conducted in 31 districts in Central Java Province. Sample was 685 children aged 11-23 months and selected using purposive and accidental sampling method. Collecting data by interview using structured questionnaire and observation with maternal and child health (MCH) Handbook to identify immunization status. The collected data was analyzed univariate, bivariate, and multivariate. As many as 74.3% of children received IPV. Partially, variables of delivery history, immunization status, knowledge, attitudes, sources of information, and service satisfaction were related to IPV adherence. Simultaneously, immunization status, attitudes, and sources of information influenced IPV adherence with an overall effect 35.2%. Immunization status as the dominant influencing factor. Efforts were needed reducing resistance to IPV through psychological approach that was motivating and personal, also using of social media as a medium for positive information and communication, in addition to improve immunization service system.